Diel cycle in a farmland bird is shaped by contrasting predation and human pressures. (17th June 2021) - Harmange, Clément; Bretagnolle, Vincent; Chabaud, Nathan; Sarasa, Mathieu; Pays, Olivier
Abstract: In human-dominated landscapes, human disturbances may contrast (spatially and/or temporally) with risk imposed by non-human predators. However, how prey adjust behaviour to minimize risk from multiple threats remains unclear. In Central-Western France, we investigated patterns of activity, space and habitat use, and causes of variations during the diel cycle of the grey partridge (captive-reared, released), a farmland bird facing multiple risks (nocturnal predation, diurnal hunting pressure). We also investigated influence of individual space use, relative to risk-related features on the fate of birds. Birds adjusted their behaviours in ways consistent with the reduction of risk from nocturnal carnivores at night and hunters during daytime. We recorded bimodal crepuscular activity, likely explained by commuting movements between spatially-separated diurnal and nocturnal sites composed of different habitats: selection of open terrains and avoidance of predator reservoirs at night vs. use of high-vegetation cover during daytime. We observed space use differences between surviving, hunted and predated birds. Predation and hunting activities act as contrasting pressures, selecting birds based on their spatial behaviour, which has likely shaped diel adjustments at the population level. An improved consideration of temporal variation in environmental pressures would help to reliably address factors constraining populations, so increasing wildlife management efficiency.